Treating fibrosing cholestatic hepatitis C with sofosbuvir and ribavirin: a matched analysis. (21st August 2015) - Saab, Sammy; Jimenez, Melissa; Bau, Sherona; Goo, Tyralee; Zhao, Difan; Durazo, Francisco; Han, Steven; El Kabany, Mohammed; Kaldas, Fady; Tong, Myron J.; Busuttil, Ronald W.
Abstract: Background: Fibrosing cholestatic hepatitis (FCH) is an uncommon but potentially fatal complication of recurrent hepatitis C (HCV) in liver transplant recipients. Methods: We matched the treatment outcomes of 10 liver transplant recipients who developed FCH with those of 10 recipients with recurrent HCV without FCH treated with sofosbuvir and ribavirin. Results: Baseline mean alanine transaminase, aspartate transaminase, alkaline phosphatase, and total bilirubin were 186 U/L, 197 U/L, 243 U/L, and 6.7 mg/dL, respectively, in the FCH recipients and 82 U/L, 60 U/L, 110 U/L, and 0.99 mg/dL, respectively, in non‐FCH recipients. The sustained viral response in FCH and non‐FCH recipients was 40% and 80%, respectively. One‐yr patient and graft survival rates were 90% and 80%, respectively, in FCH recipients, and 100% in non‐FCH recipients. Seven FCH and six non‐FCH recipients were treated for anemia with blood transfusion and/or erythropoietin growth factors. Conclusion: Our results suggest that the use of sofosbuvir and ribavirin is effective and tolerable in liver transplant recipients treated for recurrent FCH. There is a trend of lower sustained viral response, patient survival, and graft survival in the FCH recipients.